Effect of oxygen enriched atmospheres on combustion of bagasse, coal and theirs blends by thermogravimetric analysis. Issue 5 (October 2020) - Chen, Chunxiang; Huang, Yuting; Yang, Shengxiong; Qin, Songheng; Chen, Feng
Graphical abstract: Highlights: Oxy-fuel combustion of coal, bagasse and bagasse/coal blends were studied by TGA. Increasing oxygen concentration can improve combustion performance. Synergetic effect exists during co-combustion of bagasse and coal. The kinetics parameters were studied by FWO and KAS methods. Abstract: The combustion of bagasse and oxygen-enriched combustion of bagasse with coal can save nonrenewable energy and reduce the pollution emission for power generation and energy production. In this study, oxy-fuel combustion and co-combustion technology were used to evaluate the combustion characteristics of bagasse and bagasse blending with coal by thermogravimetric analysis (TGA) at different oxygen-enrich atmospheres (30 % O2 / 70 % N2, 50 % O2 / 50 % N2 and 70 % O2 / 30 % N2 ), and activation energy ( E ) was calculated using Flynn-Wall-Ozawa (FWO) and Kissinger–Akahira–Sunose (KAS) methods. The results indicated that three stages existed during the sample combustion, and the main combustion process occurred at the second stage. As oxygen concentration increased, the reaction rate at the maximum peaks ( R p ) of derivative thermogravimetric analysis (DTG), average reaction rate ( R v ), and apparent activation energy ( E ) increased, while the ignition temperature ( T i ), final temperature detected as mass stabilization ( T f ), and residue mass ( M r ) decreased. Synergistic interactions were observed during the co-combustion of bagasse and coal. The M r (3.64) of 20 % bagasse / 80 % coal was lower than that of coal (1.31) in O2 / N2 = 3/7 atmosphere. The average values of E for pure bagasse were 112.6–133.6 kJ mol ―1 at the oxygen concentration ranging from 30 % to 70 % in O2 / N2 atmosphere, while those of 20 % bagasse / 80 % coal were 145.6–161.4 kJ mol ―1 . From the perspective of efficiency, the co-combustion of bagasse and coal has complementary advantages based on low T i, T p, and high R p, R v . The results provide some useful guidance and suggestions for the power plants.